Assessing the Influence of Minimum Wage, Education, and Poverty on the Labor Force Participation Rate: Evidence from Central Java Province - Audilla, Yessiska Fina; Rachmawati, Lucky (University Merdeka Malang, 2025)
This study aims to analyze the impact of minimum wage, education, and poverty on the labor force participation rate (LFPR) in Central Java Province from 2018 to 2023. Employing an associative quantitative research design, the analysis utilizes a panel regression method with a Fixed Effect Model (FEM). The results indicate that minimum wage has a positive and significant effect on LFPR, while education shows a positive but insignificant effect. Conversely, poverty exerts a negative and significant influence on LFPR. Collectively, minimum wage, education, and poverty significantly affect labor force participation in Central Java during the specified period. These findings provide valuable insights for policymakers aiming to enhance labor market engagement through targeted wage and educational strategies.